2015
DOI: 10.1002/bin.1402
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus Fading and Response Elaboration in Differential Reinforcement for Alternative Behavior

Abstract: A hallmark of applied behavior analysis is the development of function-based interventions for problem behavior. A widely recommended function-based intervention is differential reinforcement of alternative behavior (DRA), in which reinforcement is contingent upon socially acceptable alternatives to problem behavior (e.g., teaching communication skills). Typically, DRA is introduced under rich schedules of reinforcement. Although effective for initiating behavior change, rich schedules are often impractical in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Moreover, observational studies and surveys have suggested, based on levels of engagement in school and home settings, that these items appear to be highly preferred for both children with ASD (King, Thomeczek, Voreis, & Scott, ; Shane & Albert, ) and children of typical development (Marshall, Gorely, & Biddle, ). Many empirical studies have also obtained reinforcement effects when using such devices with individuals with ASD (e.g., Kennedy & Souza, ; Schlichenmeyer, Dube, & Vargas‐Irwin, ; Shamlian et al, ), lending further support for the inclusion of these items in preference assessments. Furthermore, Fahmie et al noted that the stimuli included in their assessments were not selected based on caregiver report; therefore, it is possible that highly preferred leisure items (e.g., a favorite toy from home) may have been left out of stimulus arrays.…”
mentioning
confidence: 90%
“…Moreover, observational studies and surveys have suggested, based on levels of engagement in school and home settings, that these items appear to be highly preferred for both children with ASD (King, Thomeczek, Voreis, & Scott, ; Shane & Albert, ) and children of typical development (Marshall, Gorely, & Biddle, ). Many empirical studies have also obtained reinforcement effects when using such devices with individuals with ASD (e.g., Kennedy & Souza, ; Schlichenmeyer, Dube, & Vargas‐Irwin, ; Shamlian et al, ), lending further support for the inclusion of these items in preference assessments. Furthermore, Fahmie et al noted that the stimuli included in their assessments were not selected based on caregiver report; therefore, it is possible that highly preferred leisure items (e.g., a favorite toy from home) may have been left out of stimulus arrays.…”
mentioning
confidence: 90%
“…It is also used for some types of ASD. The therapist probes the person with ASD to unlearn an adverse behaviour and replace it with the positive one (Schlichenmeyer et al 2015).…”
Section: Fadingmentioning
confidence: 99%
“…Other topics in this section of the literature included generalization of FCRs across functional contexts (Falcomata, White, Muething, & Fragale, 2012), negatively reinforced FCRs (Yi et al, 2006), effects of response effort on response rates for mands and destructive behavior (Buckley & Newchok, 2005), and differences in obtained reinforcement and programmed reinforcement during FCT (Johnson, McComas, Thompson, & Symons, 2004). Three of these studies looked at fading the schedule of reinforcement for the FCR to be more practical (Falcomata, Muething, Gainey, Hoffman, & Fragale, 2013a;Falcomata, Wacker, Ringdahl, Vinquist, & Dutt, 2013b;Schlichenmeyer, Dube, & Vargas-Irwin, 2015). Although these studies represent a special case of mand training for which the ultimate goal was the reduction of destructive behavior, they still met the inclusion criteria for this review.…”
Section: Mandsmentioning
confidence: 99%